ANALYSIS OF THE IMPACT OF WATTPAD AS ONLINE WRITING AND READING APPLICATION TO CUSTOMER INTENTION ON BUYING PRINTED NOVEL - Millianda, Pridya Equita; Windasari, Nila Armelia (Journal of Business and Management, 2021)
Wattpad is an online website and application designed to publish new user-generated stories for novice authors, which aims at creating social networks around stories for both amateurs and established writers. Wattpad helps aspiring authors find audiences, but it also offers original content to conventional book publishers, advertisers, and film and TV producers, in addition to providing them with real-time insights on the stories and subjects audiences find exciting (Steiner, A, 2017). Since Wattpad's popularity skyrocketed in Indonesia around 2011, the fiction shelves in bookstores in Indonesia are now dominated by books adapted from Wattpad. However, despite the fact that there are a significant number of Wattpad novels in the bookshelf, there rarely is a journal that discusses the relationship between the usage of Wattpad by readers, and their intentions to buy printed Wattpad books, especially in Indonesia. Therefore, this research aims to fill the existing gap. A quantitative survey was conducted among 325 respondents who have used the Wattpad app for at least the last 6 months to meet the objective of the research. As a result, after analyzing both genders of the respondent separately, it is indicated that for females, author familiarity, customer engagement, and perceived value is significantly correlated to consumer purchase intention. It was also found that perceived value is correlated to thestory idea and customer engagement, while the engagement itself could occur depending on how interesting the story ideas, author familiarity, author’s promotion, as well as vote for vote and comment for comment activities. However, the perspective of the male respondent remains unclear because of the limitation of the number of respondents.Keywords: Wattpad Indonesia; Online writing and reading platform; Customer Engagement; Perceived Value; Purchase Intention